Тепловое и термонапряженное состояния ротора высокого давления турбины К-325-23,5 при пуске из холодного состояния - Бахмутская, Ю.О.; Голощапов, В.Н. (Проблемы машиностроения, 2017)
Выполнено расчетное исследование теплового и термонапряженного состояний ротора цилиндра высокого давления паровой турбины ПАО «Турбоатом» мощностью 325 МВт на этапах прогрева и пуска турбины из холодного состояния. Для определения нестационарного теплового состояния ротора получены тепловые граничные условия 3-го рода. Учитывался процесс конденсации пара на поверхностях элементов ротора и межкорпусного пространства. Предложено изменение конструкции и условий прогрева ротора высокого давления в области переднего концевого уплотнения на этапе подготовки к пуску из холодного состояния и показана возможность снижения уровня термических напряжений, возникающих при пуске турбины Виконане розрахункове дослідження теплового і термонапруженого станів ротора циліндра високого тиску парової турбіни ПАТ «Турбоатом» потужністю 325 МВт на етапах прогріву та пуску турбіни iз холодного стану. Для визначення нестаціонарного теплового стану ротора отримані теплові граничні умови 3-го роду. Враховувався процес конденсації пари на поверхнях елементів ротора та мiжкорпусного простору. Запропонована зміна конструкції та умов прогріву ротора високого тиску в області переднього кінцевого ущільнення на етапі підготовки до пуску з холодного стану і показана можливість зниження рівня термічних напружень, що виникають при пуску турбіни. The high-pressure turbine rotor is the most critical and costly steam turbine component. Service experience for the machines with a power of 150 MW and more shows that cracks appear in the region of regulation stage fillets and end seals in high-pressure turbine rotors. The cause of this effect can be the high thermal gradients during turbine pre-start and cold start-up. For steam turbine components, the thermal state is strongly influenced by the condensation process, which takes place during the turbine pre-start and cold start-up phase. The process continues until the rotor surface temperature becomes higher than the steam saturation temperature. Condensation heat transfer coefficients are much higher than that of calculated for the case without condensation. In this article to simulate the rotor heating process during turbine pre-start with the highest accuracy, several aspects are studied. Steam characteristics in rotor flow path and end seals regions were determined for K-325-23,5 turbine taking into the account leakages through drainages and specificity of turbine heating through exhaust hood. To determine steam parameters in front end seals chamber, which is connected to the inter-casing space, the condensation process duration in at cold start-up was determined. Thermal conditions were calculated taking into the account the condensation effect. K-325-23,5 turbine pre-start and cold start-up technology was analyzed with regards to high-pressure rotor thermal and thermal stress-strain state. Thermal and thermo-structural analyses results show that significant rotor portion in the region of front end seal stays cold for the whole period from vacuum set up to acceleration phase. Such non-rational heating at the prestart phase leads to significant thermal gradients and thermal stresses which are above the material yield strength. As a result of the study, the design improvement is suggested which is consists of additional chambers arrangement in front end seals carrier along with additional steam flow organization at the prestart phase. Such improvements allows to: 1) provide high-pressure rotor uniform heating in the front end seal region; 2) increase turbine reliability due to decreased level of thermo-stresses